2002
DOI: 10.1093/ije/31.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variation of Helicobacter pylori treatment success in adults worldwide: a meta-analysis

Abstract: More effective treatments are needed for most populations of the world where H. pylori infection in children and drug resistance are common. Current treatment guidelines do not coincide with the best treatment regimens identified in this meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
147
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(157 citation statements)
references
References 44 publications
2
147
1
Order By: Relevance
“…A triple-therapy regimen for 7 to 14 days is used as the first-line treatment for H. pylori-infected patients, but the failure rate is around 20 to 30% (7,9). The failure of antibiotic treatment has been assumed to be due to the selection of an antibiotic-resistant mutant.…”
Section: Vol 78 2010mentioning
confidence: 99%
“…A triple-therapy regimen for 7 to 14 days is used as the first-line treatment for H. pylori-infected patients, but the failure rate is around 20 to 30% (7,9). The failure of antibiotic treatment has been assumed to be due to the selection of an antibiotic-resistant mutant.…”
Section: Vol 78 2010mentioning
confidence: 99%
“…3 Although increased antimicrobial resistance has been seen with each of the agents used in treatment of H. pylori, the increase in treatment failure can be attributed in large part to resistance to clarithromycin. [4][5][6] It has been previously demonstrated that point mutations in domain V of the 23S rRNA gene are responsible for the resistance of H. pylori to macrolides, 7 with the three major point mutations being A2142G, A2143G, and A2142C. 7 The most frequent of these are transitions of adenine to guanine at the 2143 or 2142 positions, which account for 480% of clarithromycin resistance seen worldwide and B90% of resistance seen in developed countries.…”
mentioning
confidence: 99%
“…This distinction has caused considerable confusion since gastritis is often used to describe endoscopic or radiologic characteristics of the gastric mucosa rather than specific histologic findings. Epithelial cell damage and regeneration without associated inflammation is referred to as "gastropathy" [63,64].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Acute ("active") inflammation is usually associated with neutrophilic infiltration, while chronic inflammation is usually characterized by mononuclear cells, chiefly lymphocytes, plasma cells and macrophages. A practical clinicopathologic framework for the classification of gastritis and gastropathy based upon these factors can be proposed [63].…”
Section: Review Of Literaturementioning
confidence: 99%